2006
DOI: 10.1159/000092766
|View full text |Cite
|
Sign up to set email alerts
|

Bisoprolol Improves Echocardiographic Parameters of Left Ventricular Diastolic Function in Patients with Systemic Hypertension

Abstract: Left ventricular (LV) diastolic dysfunction (LVD) is a common complication secondary to hypertension. It has been reported that bisoprolol is effective in reducing blood pressure and has beneficial cardiac effects in patients with hypertension. However, its effect on LV diastolic function has not been studied in detail. In this study, we sought to determine bisoprolol’s effect on left ventricle diastolic function. Data from 25 patients were statistically analyzed. Peaks E and A wave, E/A ratio, isovolumetric r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…That led to decrease in SBP[45] and improve diastolic function in the left ventricle, which led to decrease in DBP. [46] Bu as reported by Shingala and Balaraman, 2005,[4] has an antihypertensive effect through aortic effect and vascular activity (DBP) Furthermore, it was reported that Bu reduced the SBP. [47]…”
Section: Resultsmentioning
confidence: 99%
“…That led to decrease in SBP[45] and improve diastolic function in the left ventricle, which led to decrease in DBP. [46] Bu as reported by Shingala and Balaraman, 2005,[4] has an antihypertensive effect through aortic effect and vascular activity (DBP) Furthermore, it was reported that Bu reduced the SBP. [47]…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies have used small samples sizes (8,21,24 -26) and have been underpowered to detect a difference between therapies. The majority of study durations have ranged from just a few weeks to 6 months (21,25,26), and very few studies have extended to a year of follow-up (8,24,27). Moreover, conventional echocardiography alone, which has been used in the majority of published studies, has limitations as a means of assessing LV diastolic function (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…None of the enrolled patients was taking aldosterone antagonists, which may reduce myocardial fibrosis (24). Because β-blockers may affect E/A ratio in hypertensive patients (25), a subgroup analysis was performed by excluding five patients treated with a β-blocker, but the results were not different without those patients (data not shown). Accordingly, it is suggested that improvement of diastolic function may be caused by valsartan-induced attenuation of myocardial fibrosis in the low IBS-CV group.…”
Section: Discussionmentioning
confidence: 99%